Electricity consumption as a new indicator of inequality. (August 2022) - Wu, Shimei; Li, Chuan-zhong; Wei, Chu
Abstract: Inequality is a growing public concern and economic threat. The degree of which, however, varies greatly depending on the choice of indicators for measurement. In this paper, we compare the strength and weaknesses of the existing indicators such as income and wealth and propose a new measure of inequality based on household electricity consumption. We believe that our measure has the advantage of capturing both service flows and stock values of durables, embodying both the outcome and opportunity inequality, and confronting fewer measurement issues. The new inequality measure based on electricity consumption may complement the existing ones by providing a relatively complete and well-balanced picture of the overall welfare inequality.